GEBELİĞİNDE LATERAL SİNUS TROMBOZU TANISI KOYULAN BİR OLGU SUNUMU - TUŞTAŞ, Esra; MADAZLI, Rıza; AKSU, M. Feridun; APAYDIN, Hülya (Cerrahpaşa Medical Journal, 2014)
Background.- Cerebral venous sinus thrombosis is an uncommon disease with variable signs and symptoms. It frequently affects large sinuses like superior sagittal sinus and in about 70 % of cases, congenital and acquired coagulation defects, infections, pregnancy and puerperium may be the predisposing factors. The response to the treatment and long term prognosis are well. Observation.- Left lateral sinus thrombosis was diagnosed with cranial MRI in a pregnant women at 33 weeks of gestation with presenting symptoms of headache, nause, vomiting and impairment of consciousness. The predisposing factor was chronic mastoiditis developed following dental treatment. With the proper management she delivered a healthy baby.